Building a Web Application on Microsoft Azure. - Díaz Concha, Rodrigo (linkedin.com, 2023)
Learn how to build web applications that take advantage of key Microsoft Azure services, including Azure DevOps, Azure App Service, Azure SQL, Azure Functions, and more.